Jordan products of quantum channels and their compatibility - Mark Girard (Nature Portfolio, 2021)
Establishing whether two quantum channels are compatible is a fundamental problem in quantum information. Here, the authors prove its equivalence to the quantum state marginal problem, introduce an efficient way to solve both, and draw further connection to the measurement compatibility problem.